2022
DOI: 10.1093/abm/kaac041
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hand Hygiene Behavior Using a Novel Theory-Based Intervention During the COVID-19 Pandemic

Abstract: Background Promoting the adoption of personal hygiene behaviors known to reduce the transmission of COVID-19, such as avoiding touching one’s face with unwashed hands, is important for limiting the spread of infections. Purpose We aimed to test the efficacy of a theory-based intervention to promote the avoidance of touching one’s face with unwashed hands to reduce the spread of COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…We also observed a main effect for momentary regulations (e.g., mandatory mask-wearing indoors), which is perhaps less surprising but at the same time supportive of the notion that regulations in addition to self-regulated motivation (“personal responsibility,” for a comment, see Reicher et al, 2022) can increase the adherence to recommended NPIs. Interventions to increase individual motivation for hygiene show small and inconsistent effects at best (Smith et al, 2022) and would likely profit from supporting regulatory measures.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a main effect for momentary regulations (e.g., mandatory mask-wearing indoors), which is perhaps less surprising but at the same time supportive of the notion that regulations in addition to self-regulated motivation (“personal responsibility,” for a comment, see Reicher et al, 2022) can increase the adherence to recommended NPIs. Interventions to increase individual motivation for hygiene show small and inconsistent effects at best (Smith et al, 2022) and would likely profit from supporting regulatory measures.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a main effect for momentary regulations (e.g., mandatory mask-wearing indoors), which is perhaps less surprising but at the same time supportive of the notion that regulations in addition to self-regulated motivation ("personal responsibility," for a comment, see Reicher, Michie, & West, 2022) can increase the adherence to recommended NPIs. Interventions to increase individual motivation for hygiene show small and inconsistent effects at best (Smith, Hagger, Keech, Moyers, & Hamilton, 2022) and would likely profit from supporting regulatory measures.…”
Section: Discussionmentioning
confidence: 99%
“…Power was set at 0.80, alpha was set at 0.01 (adjusted to protect from inflation of type I error rate due to multiple tests), and the correlation between repeated measures set at 0.70, which was based on previous research that observed strong correlations between repeated measures of behaviour in a HAPA-based behaviour change intervention. 76 The analysis yielded a total minimum required sample size of 118.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The effect size was set to Cohen’s f=0.10 to detect a conservatively small effect,75 which was chosen due to the lack of previous research on HAPA-based behavioural interventions among survivors of stroke which could inform the expected effect size. Power was set at 0.80, alpha was set at 0.01 (adjusted to protect from inflation of type I error rate due to multiple tests), and the correlation between repeated measures set at 0.70, which was based on previous research that observed strong correlations between repeated measures of behaviour in a HAPA-based behaviour change intervention 76. The analysis yielded a total minimum required sample size of 118.…”
Section: Methods and Analysismentioning
confidence: 99%